2009
DOI: 10.1111/j.1863-2378.2008.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

The Studies on the Aetiology of Diarrhoea in Neonatal Calves and Determination of Virulence Gene Markers ofEscherichia coliStrains by Multiplex PCR

Abstract: The purpose of this study was to determine aetiological agents of diarrhoea in neonatal calves and to investigate virulence gene markers of Escherichia coli strains isolated from calves by multiplex polymerase chain reaction (PCR). Eighty-two diarrhoeic calves and 18 healthy calves were used as subjects. Faeces were taken from the rectums of all the calves and were subjected to bacterial culture. Antigen enzyme-linked immunosorbent assay (ELISA) was performed to detect rotavirus, coronavirus and E. coli K99 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 33 publications
(60 reference statements)
7
42
1
8
Order By: Relevance
“…K99 and/or F41 fimbriae, the major adhesion factors, mediate adherence to the ileum [3,12] and have been found in most E. coli isolates from diarrheic calves [3,10]. In this study, however, fanC and fim41a, the genes for F4 and F41 fimbriae, were detected in 9.9 and 8.3%, respectively, which are relatively lower rates compared to those previously reported [3,12,14]. Recently, the F17 fimbrial family has been known to be prevalent in PEC strains isolated from calves with diarrhea or septicemia [12,15].…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…K99 and/or F41 fimbriae, the major adhesion factors, mediate adherence to the ileum [3,12] and have been found in most E. coli isolates from diarrheic calves [3,10]. In this study, however, fanC and fim41a, the genes for F4 and F41 fimbriae, were detected in 9.9 and 8.3%, respectively, which are relatively lower rates compared to those previously reported [3,12,14]. Recently, the F17 fimbrial family has been known to be prevalent in PEC strains isolated from calves with diarrhea or septicemia [12,15].…”
contrasting
confidence: 74%
“…Although virulence factors such as intimin and Shiga toxins are associated with diarrhea in calves [12,13], the virulence factors are in high rate isolated from feces of healthy calves and cattle [3,5,14,16]. However, the strain containing virulence factors of Shiga toxins and intimin are associated with cases of gastroenteritis in humans, which could progress to hemorrhagic colitis and hemolytic uremic syndrome [4,13].…”
mentioning
confidence: 99%
“…Epidemiological studies on the 'Guidelines for Animal Experimentation' approved diarrhoea in lambs have shown that Escherichia coli is by the Institutional Animal Care Committee. an important cause of neonatal mortality [2,3].…”
Section: Methodsmentioning
confidence: 99%
“…The cryptosporidial colonization of the small and large intestine results in destruction of enterocytes. Contrary to isolated bacterial or viral infections, mixed infections with C. parvum are associated with shortening of intestinal villi and persistent severe disorders of digestion and absorption (Coutinho et al 2008, Ok et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…While the diarrhea of neonatal calves is usually associated with bacterial (E. coli) or rotaviruses and coronaviruses infections, Cryptosporidium spp. seems to be the most common cause of diarrhea in older, 3-week-old animals (Coutinho et al 2008, Foster and Smith 2009, Ok et al 2009). Clinical signs of diarrhea include loose watery stools, lack of appetite and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%